Elevational differences in hydrogeomorphic disturbance regime influence sediment residence times within mountain river corridors - Nicholas A. Sutfin (Nature Portfolio, 2019)
Extreme climatic events and wildfires can potentially influence sediment residence times in rivers, although the effect is not clear. Here, the authors present radiocarbon ages to show mountain streams as stable retentive reservoirs poised to change under shifting hydrologic and fire regimes.